PENGARUH KONSENTRASI PIGMEN WARNA DARI DAUN PACAR KUKU (Lawsonia inermis L.) TERHADAP EFISIENSI DYE SENSITIZED SOLAR CELL (DSSC) - Yulia Kirana Lahsmin; Iswadi Iswadi; Aisyah Aisyah; Rahmaniah Rahmaniah (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2018)
There was research on Dye Sensitized Solar Cell to determine the effect of concentration Henna (Lawsonia inermis L.) leaves pigments on the efficiency of DSSC. The solar cell is made with a sandwich structure, the dye used is made in three variations of concentration is concentration of 10%, 20% and 30%. TiO2 deposition on ITO glass made using the method of doctor blade with a cell area of 2.25 cm2 for 24 hours of immersion in the dye. Based on the results of measurements of IV by using a source of light, DSSC efficiency for dye obtained with a concentration of 30% which is 0.003366667%, to dye with a concentration of 20% is 0.0033264% and to dye with a concentration of 10% which is 0.000312%. This research can be concluded that the higher the concentration of dye used, the higher the efficiency of DSSC generated.